Influence of organizational culture, leadership and decision making on employee performance at the Ministry of Defense of the Republic of Indonesia - Nina Ruslinawati; Syarief Gerald Prasetya (STIE Binaniaga, 2021)
Abstract: The research is intended to explain the relationship between employee performance and organizational culture, leadership and decision making. The research used 100 randomly selected samples and analyzed the data using path analysis by inserting all variables into the correlation matrix. The results of the analysis showed decision making was directly influenced by organizational culture and leadership. Then the performance of employees is directly and indirectly influenced by leadership and decision making. But the performance of employees is not directly illuminated by the culture of the organization. Based on the findings explained that variations in employee performance changes can occur due to influenced organizational culture, leadership and decision making. Therefore, the management of employee performance, organizational culture, leadership and decision making should be included in the strategic plan of human resource development at the Ministry of Defense of the Republic of Indonesia. The need to include other variables to estimate employee performance in subsequent research.Keywords: organizational culture, leadership, decision making, employee performance